Promoting Uptake of COVID-19, Influenza, and RSV Vaccines for Fall 2023 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Fall 2023 marks the first time that vaccines for three respiratory illnesses - COVID-19, seasonal influenza, and respiratory syncytial virus (RSV) - will be available simultaneously. If taken, these vaccines can mitigate increases in cases, hospitalizations, and deaths that could strain the healthcare system, negatively impact the economy, and add to stress for individuals and families over the coming months. This publication describes vaccination strategies for fall 2023 that are based on current research in science communication, decision making, sociology, anthropology, and social psychology. Produced through the Societal Experts Action Network (SEAN), this rapid expert consultation links researchers in the social, behavioral, and economic sciences with decision makers to provide actionable guidance on critical and complex issues, including those related to the COVID-19 pandemic.
Keywords: Health and Medicine

2020 Census Data Products: Demographic and Housing Characteristics File: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
This proceedings summarizes the presentations and discussions at the Workshop on the 2020 Census Demographic and Housing Characteristics File, held June 21-22, 2022. The workshop was convened by the Committee on National Statistics of the National Academies of Sciences, Engineering, and Medicine to assist the U.S. Census Bureau with its new disclosure avoidance system for 2020 Census data products, which implements algorithms providing differential privacy. The workshop focused specifically on the Demographic and Housing Characteristics File, a major source of data for local governments, particularly those with small populations, and many other data users in the federal, state, academic, and business sectors. The intent was to garner feedback from users on the usability of the privacy-protected data by evaluating DHC demonstration files produced with the proposed TopDown Algorithm on 2010 Census data.
Keywords: Behavioral and Social Sciences

Spatial Justice as a Driver of Health in the Context of Societal Emergencies: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Spatial justice is about equitable access to parks, housing, and more. During societal emergencies, including pandemics and climate change, the relationship between people and places requires greater attention and action to integrate the knowledge of people with lived experience, especially historically marginalized communities. On September 20 and 21, 2021, the National Academies Roundtable on Population Health Improvement hosted a virtual workshop to explore the nature, use, design of, threats, and changes to places as a resource for health and public spaces as a shared resource. This Proceedings document summarizes workshop discussions.
Keywords: Health and Medicine

Assisted Resettlement and Community Viability on Louisiana's Gulf Coast: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In 2021, the Gulf Research Program of the National Academies of Sciences, Engineering, and Medicine sponsored a two-year consensus study, Managed Retreat in the U.S. Gulf Coast Region, to examine and make findings and recommendations regarding the unique challenges associated with managed retreat among vulnerable coastal communities in the region. To gather information for the consensus report, the authoring committee convened a series of three public workshops in the Gulf Coast region. The workshops, held in June and July of 2022, focused on policy and practice considerations, research and data needs, and community engagement strategies. This publication summarizes the presentations and discussions of the workshops.
Keywords: Behavioral and Social Sciences

Using Population Descriptors in Genetics and Genomics Research: A New Framework for an Evolving Field - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Genetic and genomic information has become far more accessible, and research using human genetic data has grown exponentially over the past decade. Genetics and genomics research is now being conducted by a wide range of investigators across disciplines, who often use population descriptors inconsistently and/or inappropriately to capture the complex patterns of continuous human genetic variation. In response to a request from the National Institutes of Health, the National Academies assembled an interdisciplinary committee of expert volunteers to conduct a study to review and assess existing methodologies, benefits, and challenges in using race, ethnicity, ancestry, and other population descriptors in genomics research. The resulting report focuses on understanding the current use of population descriptors in genomics research, examining best practices for researchers, and identifying processes for adopting best practices within the biomedical and scientific communities.
Keywords: Health and Medicine; Behavioral and Social Sciences

Reducing Racial Inequality in Crime and Justice: Science, Practice, and Policy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The history of the U.S. criminal justice system is marked by racial inequality and sustained by present day policy. Large racial and ethnic disparities exist across the several stages of criminal legal processing, including in arrests, pre-trial detention, and sentencing and incarceration, among others, with Black, Latino, and Native Americans experiencing worse outcomes. The historical legacy of racial exclusion and structural inequalities form the social context for racial inequalities in crime and criminal justice. Racial inequality can drive disparities in crime, victimization, and system involvement. Reducing Racial Inequality in Crime and Justice: Science, Practice, and Policy synthesizes the evidence on community-based solutions, noncriminal policy interventions, and criminal justice reforms, charting a path toward the reduction of racial inequalities by minimizing harm in ways that also improve community safety. Reversing the effects of structural racism and severing the close connections between racial inequality, criminal harms such as violence, and criminal justice involvement will involve fostering local innovation and evaluation, and coordinating local initiatives with state and federal leadership. This report also highlights the challenge of creating an accurate, national picture of racial inequality in crime and justice: there is a lack of consistent, reliable data, as well as data transparency and accountability. While the available data points toward trends that Black, Latino, and Native American individuals are overrepresented in the criminal justice system and given more severe punishments compared to White individuals, opportunities for improving research should be explored to better inform decision-making.
Keywords: Behavioral and Social Sciences

Toward a 21st Century National Data Infrastructure: Mobilizing Information for the Common Good - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Historically, the U.S. national data infrastructure has relied on the operations of the federal statistical system and the data assets that it holds. Throughout the 20th century, federal statistical agencies aggregated survey responses of households and businesses to produce information about the nation and diverse subpopulations. The statistics created from such surveys provide most of what people know about the well-being of society, including health, education, employment, safety, housing, and food security. The surveys also contribute to an infrastructure for empirical social- and economic-sciences research. Research using survey-response data, with strict privacy protections, led to important discoveries about the causes and consequences of important societal challenges and also informed policymakers. Like other infrastructure, people can easily take these essential statistics for granted. Only when they are threatened do people recognize the need to protect them. Toward a 21st Century National Data Infrastructure: Mobilizing Information for the Common Good develops a vision for a new data infrastructure for national statistics and social and economic research in the 21st century. This report describes how the country can improve the statistical information so critical to shaping the nation's future, by mobilizing data assets and blending them with existing survey data.
Keywords: Behavioral and Social Sciences

Advancing Antiracism, Diversity, Equity, and Inclusion in STEMM Organizations: Beyond Broadening Participation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Individuals from minoritized racial and ethnic groups continue to face systemic barriers that impede their ability to access, persist, and thrive in science, technology, engineering, mathematics, and medicine (STEMM) higher education and workforce. Without actively dismantling policies and practices that disadvantage people from minoritized groups, STEMM organizations stand to lose much needed talent and innovation as well as the ideas that come from having a diverse workforce. A new report from the Board on Behavioral, Cognitive, and Sensory Sciences examines the backdrop of systemic racism in the United States that has harmed and continues to harm people from minoritized groups, which is critical for understanding the unequal representation in STEMM. The report outlines actions that top leaders and gatekeepers in STEMM organizations, such as presidents and chief executive officers, can take to foster a culture and climate of antiracism, diversity, equity, and inclusion that is genuinely accessible and supportive to all.
Keywords: Behavioral and Social Sciences

Civic Engagement and Civic Infrastructure to Advance Health Equity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
There is increasing evidence that civic participation - from voting to volunteering - is a social driver of health. The National Academies of Sciences, Engineering, and Medicine's Roundtable on Population Health Improvement convened a workshop to explore the links between civics and health; between measures of civic engagement and quantitative and qualitative measures of health equity; and the roles that civic infrastructure, narrative, and media play in shaping civic engagement. Presenters discussed voting along with other important dimensions of civic engagement; others include the ability to set agendas, shape how policies are implemented, communicate information, model civic behavior, and support the involvement and inclusion of other individuals and groups.
Keywords: Health and Medicine

Addressing COVID-19–Related Challenges Facing Individuals Engaged in Precarious Employment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic has exacerbated challenges facing workers engaged in precarious employment - those in positions commonly characterized by little to no job security, low wages, and few or no benefits. Through the first three years of the pandemic, many of these workers reported increased exposure to COVID-19, limited access to sick leave, job losses, and reduced hours. The latest guidance from the Societal Experts Action Network (SEAN) identifies strategies that state and local decision makers can use to mitigate COVID-19-related challenges facing individuals engaged in precarious employment, with particular attention to strategies that can remedy existing inequalities.
Keywords: Behavioral and Social Sciences

Committee on Human Rights: Annual Report 2022 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
With the support of the National Academies leadership and the more than 1,500 Academy members who actively support our work, the Committee on Human Rights (CHR) continues to assist colleagues under threat around the world and integrate human rights into the work of the National Academies. This publication highlights the assistance provided by CHR to at-risk colleagues and advocacy work and events hosted by CHR during 2022 to draw attention to colleagues suffering human rights abuses as a consequence of their professional activities and their exercise of internationally protected rights.
Keywords: Behavioral and Social Sciences

Representing Lived Experience in the Climate and Economic Justice Screening Tool: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
This new publication presents highlights of a June 2023 workshop that focused on a new geospatial tool developed by the White House Council on Environmental Quality to identify communities experiencing climate and economic burdens. The tool, called the Climate and Economic Justice Screening Tool, will be used to guide federal investments to further the White House’s Justice40 Initiative. The workshop explored how well data in the tool represents the lived experiences of historically marginalized and overburdened communities in the United States. Participants included researchers, policy makers and community members from a wide range of regional, cultural, ethnic, and socioeconomic backgrounds. Topics discussed included potential data gaps, the impact of climate and economic burdens, regional differences in data, historical factors that affect community health and wellbeing, and other inputs to the tool that might help it accurately identify disadvantaged communities.This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

Strategic Innovation and Commercialization: Supporting IP and Tech Transfer to Advance U.S. Research Competitiveness: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On February 7-8, 2023, the Government-University-Industry Research Roundtable of the National Academies of Science, Engineering, and Medicine convened a workshop for its membership and invited guests to discuss how to foster the health and productivity of the U.S. research enterprise in the context of challenges and potential solutions driven by new partnerships and other opportunities related to economic security and competition. The workshop considered critical elements to promote and strengthen research commercialization, including new protection and security frameworks for intellectual property, advancement of U.S. leadership in international standards organizations, and best practices to promote technology transfer. This publication summarizes the presentations and discussion of the workshop.
Keywords: Policy for Science and Technology

Understanding the Rules of Life Program: Scientific Advancements and Future Opportunities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In 2023, the National Academies held a series of facilitated workshops to gather information on progress to date on projects funded by the National Science Foundation (NSF) Understanding the Rules of Life (URoL) program. A fundamental goal of the URoL program is to identify the causal, predictive relationships that drive how life functions—a concept articulated as the "rules of life." Principal investigators of the URoL program shared findings from their research and how those findings might contribute to identifying rules of life that are generalizable across fields and scales. Participants also discussed how they have incorporated multidisciplinary, systems-level approaches into their work. This booklet highlights the program's focus areas and reach, major scientific breakthroughs, and lessons for research and education across scientific disciplines. This booklet is intended for policy and lay audiences interested in learning more about the goals and opportunities of NSF's URoL program.
Keywords: Biology and Life Sciences

Barriers, Challenges, and Supports for Family Caregivers in Science, Engineering, and Medicine: Proceedings of Two Symposia - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Before the COVID-19 pandemic, research demonstrated a significant impact of family caregiving responsibilities on the careers of professionals who work in science, technology, engineering, mathematics, and medicine (STEMM) - especially women. The COVID-19 pandemic increased public recognition of the challenges experienced by caregivers in STEMM fields and created a sense of urgency among many stakeholders. As part of the information-gathering stage of a forthcoming consensus study to address the barriers faced by caregivers, of all genders, in STEMM fields, the Committee on Policies and Practices for Supporting Family Caregivers Working in Science, Engineering, and Medicine organized two national symposia on February 27 and March 27, 2023. Scholars and leaders from a range of sectors convened to identify evidence-based interventions that can support the recruitment, retention, and advancement of caregivers in science, engineering, and medical fields. This publication summarizes the presentations and discussion of the symposia.
Keywords: Policy for Science and Technology

Evaluation of Compensation Data Collected Through the EEO-1 Form - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The U.S. Equal Employment Opportunity Commission (EEOC) expanded EEO-1 data collection for reporting years 2017 to 2018 in an effort to improve its ability to investigate and address pay disparities between women and men and between different racial and ethnic groups. These pay disparities are well documented in national statistics. For example, the U.S. Census Bureau (2021) found that Black and Hispanic women earned only 63 percent and 55 percent as much, respectively, of what non-Hispanic White men earned. Evaluation of Compensation Data Collected Through the EEO-1 Form examines the quality of pay data collected using the EEO-1 form and provides recommendations for future data collection efforts. The report finds that there is value in the expanded EEO-1 data, which are unique among federal surveys by providing employee pay, occupation, and demographic data at the employer level. Nonetheless, both short-term and longer-term improvements are recommended to address significant concerns in employer coverage, conceptual definitions, data measurement, and collection protocols. If implemented, these recommendations could improve the breadth and strength of EEOC data for addressing pay equity, potentially reduce employer burden, and better support employer self-assessment.
Keywords: Behavioral and Social Sciences

U.S. Health Care Expenditures: Costs, Lessons, and Opportunities: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Roundtable on Population Health Improvement, a convening activity of the National Academies of Sciences, Engineering, and Medicine, held a workshop on March 15-16, 2021, to explore issues related to increasing health care spending in the United States. The workshop, U.S. Health Care Expenditures: Costs, Lessons, and Opportunities, was organized to highlight the persisting challenge of health care expenditures that are not commensurate with the health outcomes they produce. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

The State of Anti-Black Racism in the United States: Reflections and Solutions from the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The mission of the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine at the National Academies of Sciences, Engineering, and Medicine is to advance discussions on the barriers and opportunities encountered by Black students and professionals as they navigate the pathways from K-12 and postsecondary education to careers in science, engineering, and medicine (SEM) and highlight promising practices for increasing the representation, retention, and inclusiveness of Black men and Black women in SEM. This proceedings serves as a summary of the presentations and discussions from a capstone workshop, held virtually on December 6 and 7, 2021, to review how anti-Black racism had permeated across the topics covered by the Roundtable over the previous 2 years.
Keywords: Policy for Science and Technology

Addressing the Long-Term Effects of the COVID-19 Pandemic on Children and Families - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic has had an unprecedented impact on the lives of children and their families, who have faced innumerable challenges such as illness and death; school closures; social isolation; financial hardship; food insecurity; deleterious mental health effects; and difficulties accessing health care. In almost every outcome related to social, emotional, behavioral, educational, mental, physical, and economic health and well-being, families identifying as Black, Latino, and Native American, and those with low incomes, have disproportionately borne the brunt of the negative effects of the pandemic. The effects of the COVID-19 pandemic on children and families will be felt for years to come. While these long-term effects are unknown, they are likely to have particularly significant implications for children and families from racially and ethnically minoritized communities and with low incomes. Addressing the Long-Term Effects of the COVID-19 Pandemic on Children and Families identifies social, emotional, behavioral, educational, mental, physical, and economic effects of the COVID-19 pandemic and looks at strategies for addressing the challenges and obstacles that the pandemic introduced for children and families in marginalized communities. This report provides recommendations for programs, supports, and interventions to counteract the negative effects of the pandemic on child and family well-being and offers a path forward to recover from the harms of the pandemic, address inequities, and prepare for the future.
Keywords: Behavioral and Social Sciences

Federal Policy to Advance Racial, Ethnic, and Tribal Health Equity - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Racially and ethnically minoritized populations and tribal communities often face preventable inequities in health outcomes due to structural disadvantages and diminished opportunities around health care, employment, education, and more. Federal Policy to Advance Racial, Ethnic, and Tribal Health Equity analyzes how past and current federal policies may create, maintain, and/or amplify racial, ethnic, and tribal health inequities. This report identifies key features of policies that have served to reduce inequities and makes recommendations to help achieve racial, ethnic, and tribal health equity.
Keywords: Health and Medicine